Analisis Kuat Tekan Beton yang Menggunakan Pasir Laut sebagai Agregat Halus pada Beberapa Quarry di Kabupaten Fakfak - Imran, Imran; Yunus, Muhammad (INTEK: Jurnal Penelitian, 2017)
SNI 03-6861-1-2002, states that the fine aggregate used in concrete structures should use river sand. However, the use of fine aggregate in Fakfak regency in general is still dependent on sea sand potential is quite large. The purpose of this study were: 1) determine the characteristics of sea sand in Fakfak regency as a component of the concrete mix; 2) determine the strength of concrete resulting from the use of sea sand. This research is an experimental research laboratory by means of sample testing and analysis of the characteristics of aggregates and concrete compressive test using a compression test machine. Results of testing the characteristics of fine aggregate to quarry in Fakfak regency consisting of quarry Kampung Seberang, quarry Kampung Sungai, quarry Tanjung Wagom and coarse aggregate from the quarry Kayuni can generally be used for a mixture of concrete for eligible characteristics of concrete aggregate but fine aggregate (sand) it is best to Tanjung Wagom quarry because of the fineness modulus 2.93 and included in zone 2. Compressive strength characteristics resulting from the quarry Kampung Seberang 122.84 kg/cm2 quarry Kampung Sungai 129.59 kg/cm2 and quarry Kampung Tanjung Wagom 144.27 kg/cm2 of the planned concrete quality 250 kg/cm2 or down 50.86% , quarry Kampung Sungai 48.16% and quarry Tanjung Wagom 42.29% down or strength is only reached at quarry Kampung Seberang 49.14%, quarry Kampung Sungai 51.84% and quarry Tanjung Wagom down 57.71%